Fluid-fluid demixing of off-critical colloid-polymer systems confined between parallel plates. - Jamie, E; Dullens, R; Aarts, D (2012)
We investigate the off-critical demixing of colloid-polymer systems confined between two parallel plates, where the surface potential is short ranged. We study the case where the minority phase completely wets the surfaces. We find that initially the sample separates as in bulk, until the size of the domains becomes sufficiently large such that further growth is restricted by the plate spacing. The behaviour of the droplets is then determined by the wettability of the walls. We furthermore explore a sample where the loss of wetting phase material to the surfaces causes a shift from a morphology associated with an unstable sample, showing spinodal decomposition, to that associated with a metastable sample. This underlines the importance of the rich interplay between the viscosity contrast and the local volume fraction on the observed morphologies.